DEVELOPMENT OF INORGANIC CHEMISTRY OF TRANSITIONAL CHEMISTRY MATERIALS IN CHEMISTRY DEPARTMENT - Maharani, Dina Kartika; Dwiningsih, Kusumawati; Hidayah, Rusly (JCER (Journal of Chemistry Education Research), 2019)
Learning materials have been developed in inorganic chemistry elements of transition elements have been developed online. The flow of the development model suggested by Thiagarajan, Semmel, and Semmel is 4-D (four D Models). This model consists of 4 stages of development, namely Define, Design, Develop, and Disseminate, but in this study it is limited to the develop stage. Based on the results of observations of student activities and student response questionnaires, it can be concluded that the material in the Inorganic Chemistry of the Transition Element is feasible.Â